Microbiology and antibiotic sensitivity pattern of peritonsillar abscess - Choolakkaparambu Aboobakker, Anwar Sadath; Sreedhar, Sandeep; Jacob, Amith; Anchukandan, Abdulla (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Peritonsillar abscess is a life threatening infection which requires immediate attention and care. If not treated immediately it may lead to several complications. But the culture and sensitivity results can be obtained after a minimum of 72 hours and hence empirical antibiotic therapy is needed. The objective of the study was to study the microbiological profile of peritonsillar abscess and the antibiotic sensitivity pattern of peritonsillar abscess. Methods: This cross sectional study was carried out on 47 quinsy patients who attended the ENT OPD of a tertiary care hospital. Abscess was drained and the pus was sent for culture and sensitivity. Results: 65.95% of the study population were males. prevalence of peritonsillar abscess was high in the age group of 21-30 (42.55%). Only one patient had bilateral abscess. Group-A beta hemolytic streptococcus was the common organism isolated followed by Staphyloccus aureus. Fluroquinolones and cefotaxime had a better sensitivity to nearly all the organisms. Conclusions: Staphylococcus and Streptococcus were the highly prevalent organisms. Immediate empirical antibiotic therapy must be advocated after draining the collection.